The Influence of Spiritual Leadership on Employee Performance with Organizational Commitment as an Intervening Variable (A Case Study at the Airport Operations Office of Andi Jemma Masamba) - Kurniawan, Andi; Y, Ria Mardiana; Hakim, Wardhani (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Spiritual leadership encompasses the values, attitudes, and behaviors required to intrinsically motivate oneself and others; thus, both leaders and followers experience spiritual well-being. This, in turn, enhances organizational commitment and productivity. This study aims to determine the influence of spiritual leadership on employee performance through organizational commitment as an intervening variable at the administrative office of Andi Jemma Masamba Airport. This research employs both quantitative and qualitative methods. It begins with the collection and analysis of quantitative data, followed by the collection and analysis of qualitative data to further explain or develop the quantitative findings. Primary data were collected through questionnaires distributed to 31 employees and analyzed using the SMART PLS version 4.1.0.4 application. The results of the study indicate that spiritual leadership has a positive and significant effect on organizational commitment, with a coefficient value of 0.753 and a p-value of 0.000 < 0.05. Spiritual leadership also has a positive and significant effect on employee performance, with a coefficient value of 0.406 and a p-value of 0.026 < 0.05. Furthermore, spiritual leadership positively and significantly affects employee performance through organizational commitment as an intervening variable, with a coefficient value of 0.344 and a p-value of 0.024 < 0.05. Organizational commitment itself has a positive and significant effect on employee performance, with a coefficient value of 0.457 and a p-value of 0.019 < 0.05. These findings provide empirical evidence that spiritual leadership and organizational commitment positively and significantly enhance employee performance.